2014
DOI: 10.3928/01477447-20140825-58
|View full text |Cite
|
Sign up to set email alerts
|

Closed Reduction and K-Wiring With the Kapandji Technique for Completely Displaced Pediatric Distal Radial Fractures

Abstract: In completely displaced pediatric distal radial fractures, achieving satisfactory reduction with closed manipulation and maintenance of reduction with casting is difficult. Although the Kapandji technique of K-wiring is widely practiced for distal radial fracture fixation in adults, it is rarely used in pediatric acute fractures. Forty-six completely displaced distal radial fractures in children 7 to 14 years old were treated with closed reduction and K-wire fixation. One or 2 intrafocal K-wires were used to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…2,5,17,26,34,39 The incidence of reduction loss can be lowered considerably by surgically adding stability to those fractures that are most prone to lose reduction. 2,40 The results of this study showed that fractures with initial complete fracture displacement and any residual fracture displacement (>0%) are prone to lose reduction and require a more frequent follow-up schedule, or even a more initial stable surgical treatment regime.…”
Section: Discussionmentioning
confidence: 87%
“…2,5,17,26,34,39 The incidence of reduction loss can be lowered considerably by surgically adding stability to those fractures that are most prone to lose reduction. 2,40 The results of this study showed that fractures with initial complete fracture displacement and any residual fracture displacement (>0%) are prone to lose reduction and require a more frequent follow-up schedule, or even a more initial stable surgical treatment regime.…”
Section: Discussionmentioning
confidence: 87%
“…However, open reduction is traumatic, bleeding, leaving surgical scars, and even a certain probability of damaging epiphysis, resulting in growth arrest and other serious complications. Some scholars used minimally invasive prying reduction technique of Kirschner wires in the treatment of irreducible distal radius fractures in children [19,20]. Pavone et al reported the midterm results of surgical treatment of displaced proximal humeral fractures in children [21].…”
Section: Discussionmentioning
confidence: 99%
“… 19 Distal radius fractures can usually be treated by closed reduction and non-invasive fixation in most of the cases. 20 However, for extra-articular or minimally displaced intra-articular fractures that are not stable with closed reduction and external fixation, surgical fixation should be performed. Likewise, in the present study, we initially applied closed reduction and circular casting in all the patients.…”
Section: Discussionmentioning
confidence: 99%